Biological versus chemical control of fall armyworm and Lepidoptera stem borers of maize (Zea mays) - Kammo, E.Q.; Suh, C.; Mbong, G.A.; Djomo, S.H.; Chimi, N.L.L.; Mbeungang, D.L.; Mafouasson, H.; Meseka, S.; Menkir, A. (2019)
Insect pests are serious constraints to production of maize. There is little information on the control measures against those insects in Cameroon. This study was carried out to identify the different species of fall armyworm and stem borers of maize and test the efficacy of different control methods. The maize variety ATP (Acid Tolerant Population) was used in a randomized complete block design. Synthetic insecticides, lambda cyalothrine and cypermethrin, were applied at one and two weeks intervals at the recommended doses of 2 L/ha and 1.5 l/ha respectively. Bio insecticides: Neem oil (Azadirachta indica), and aqueous extracts of Chenopodium ambrosioides leaves were applied weekly at the doses of 1.40 L/ha and 6.80 L/ha respectively. The different larvae recorded were the fall armyworm (Spodoptera frugiperda) and stem borers (Busseola fusca and Sesamia calamistis). All the treatments used in this study had significant effects on the number of pupae, the tunnels and the number of perforations on stems of the maize. The Neem oil at one-week interval was more effective in reducing the incidence (81, 21%) and severity (61, 54%) at 76 Days After Planting of the attack by the caterpillars as well as on the number of larvae (14, 82%) throughout the trial.